Ultrasmall superparamagnetic iron oxide nanoparticles coated with fucoidan for molecular MRI of intraluminal thrombus. (January 2015) - Suzuki, Michimasa; Bachelet-Violette, Laure; Rouzet, François; Beilvert, Anne; Autret, Gwennhael; Maire, Murielle; Menager, Christine; Louedec, Liliane; Choqueux, Christine; Saboural, Pierre; Haddad, Oualid; Chauvierre, Cédric; et al.
Aim: We have designed ultrasmall superparamagnetic iron oxide (USPIO) nanoparticles associated with fucoidan (USPOI-FUCO), a natural sulfated polysaccharide with high affinity for activated platelets, to visualize by MRI arterial thrombi.Materials & methods : USPIOs were prepared and sizes, zeta-potentials and relaxivities were measured. Elastase perfusion in the infrarenal aorta of Wistar rats induced intraluminal thrombus. They were scanned on 4.7 T MRI before and after injection of USPIO-FUCO or USPIO coated with anionic dextran.Results: Surface plasmon resonance evidenced that fucoidan and USPIO-FUCO bind in vitro to immobilized P-selectin. All intraluminal hyposignals detected by MRI after injection of USPIO-FUCO on animals (13 out of 13) were correlated by histology with thrombi, whereas none could be identified with control USPIOs (0 out of 7). No signal was seen in absence of thrombus. Thrombi by MRI were correlated with P-selectin immunostaining and USPIO detection by electron microscopy.Conclusion:   In vivo thrombi can thus be evidenced by MRI with USPIO-FUCO. Original submitted 8 July 2013; Revised submitted 4 March 2014